The impact of the information gap strategy on developing skills and classroom interaction among students of the Department of Art Education (Journal of the College of Basic Education, 2024)
current research aims to identify” the impact of the information gap strategy to develop classroom interaction skills for students of the Department of Art Education in the course of general teaching methods”.The first chapter shows the problem of the study and its significance, and defines the basic terms. The second chapter includes the theoretical framework and it discusses the information gap strategy and patterns of classroom interaction and its importance in teaching , also it sheds the light on the previous researches that are related to the present study. The third chapter states procedures of the study: deciding the appropriate experimental design for the research, selecting the (population and sample) and controlling variables, and constructing instrument of the study , leading to the application of the experiment and showing statistical tools usedIn the fourth chapter, the researcher found out that the experimental group (which was taught using the information gap strategy and classroom interaction) outperformed the control group.Finally the researcher has drawn some conclusion, recommendations, and suggestions for further studies